Evaluation of 2009 pandemic influenza A (H1N1) exposures and illness among physicians in training - de Perio, Marie A. (Am J Infect Control, 2012)
BACKGROUND: A cluster of influenza-like illness (ILI) among physicians in training during the 2009 influenza A (H1N1) pandemic (pH1N1) led to a health hazard evaluation. METHODS: We conducted a cross-sectional study to examine exposures, infection control practices, ILI prevalence, and transmission among physicians in training at 4 affiliated hospitals during the pandemic. We administered an electronic survey and met with physicians in training and hospital personnel. RESULTS: Of the 88 responding physicians, 85% reported exposure to pH1N1. Exposures occurred at work from patients or coworkers and outside of work from coworkers, household members, or the community. Thirteen cases of ILI were reported in May-June 2009; 10 respondents reported working while ill (duration, 1-4 days). Between 13% and 88% of respondents knew which personal protective equipment (PPE) was recommended when caring for influenza patients at the 4 hospitals. The most common reasons for not using PPE were not knowing that a patient had pH1N1 or ILI and not having PPE readily available. CONCLUSIONS: Physicians in training have gaps in their knowledge of and adherence to recommended PPE and compliance with work restrictions. Our findings underscore the importance of installing isolation precaution signage, making PPE readily available near patients with influenza, and facilitating work restrictions for ill health care personnel.